Research of the Actual Path for Hybrid Input Five-bar Mechanism - Lin Bin; Yu Haiyan; Zhang Wenjun (Jixie chuandong)
While the hybrid input five-bar mechanism in the process of actual movement,constant velocity motor will generate speed fluctuation,as a result terminal actuator will come out path error.An actual path synthesis method in consideration of hybrid input mechanism dynamics is proposed in order to generate much more accurate path.By means of five times spline functions interpolation method making the ideal path of servo motor second-order continuous,the dynamics model of hybrid input mechanism which in consideration of motor dynamics is given,the calculation of the dynamics model is described,with the input of the servo motor as design variables to reduce the path error of end executor.Example simulation certifies that the path of the proposed method can generate more accurate path.